“Cognitive Grammar in English and Uzbek” (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
The aim of this thesis is to explore the similarities and differences in cognitive grammar as applied to English and Uzbek, emphasizing how cultural contexts shape cognitive processes associated with language use and highlighting structural and aspectual distinctions between the two languages.